If it's not what You are looking for type in the equation solver your own equation and let us solve it.
68=3x+2(-4x+9)
We move all terms to the left:
68-(3x+2(-4x+9))=0
We calculate terms in parentheses: -(3x+2(-4x+9)), so:We get rid of parentheses
3x+2(-4x+9)
We multiply parentheses
3x-8x+18
We add all the numbers together, and all the variables
-5x+18
Back to the equation:
-(-5x+18)
5x-18+68=0
We add all the numbers together, and all the variables
5x+50=0
We move all terms containing x to the left, all other terms to the right
5x=-50
x=-50/5
x=-10
| -3x-2(-3x+13)=1 | | 15w-22=128 | | 3p-7=|p+5| | | 5.6+18-1.3x=0.9(x-0.4 | | 15+x=-25 | | -200÷x=-20 | | x/5+12=50 | | (3-5x)/2=0 | | 87+44+x=180 | | 7x+43=39,5 | | -(3x-8)=40 | | -182=-4m–5(3m+6) | | 17a+15=-76 | | -20+m=40 | | 6-2y+y=22 | | x-2/x+5=6/20 | | -2xX-7,X=10 | | 3(x+8)=58 | | x-5=124/(45-x-5) | | -7(x+1)+2x=-32 | | -2(2x+7)-1=3(x-5)+9 | | 5x+27=34 | | 3x–6+7x–6=x+9+2x+7 | | 5y-12,y=-8 | | 4x+3x–2x=132–72 | | 3=4/3(8x−6)3 | | 55-5z=3(z-3) | | 2(3u-7)=-4(3-2u) | | 9x-16=10x-10 | | Y=80^c | | -3x+4,X=5 | | 7v+4=4v+22 |